2015
DOI: 10.1093/gji/ggv111
|View full text |Cite|
|
Sign up to set email alerts
|

Aseismic transient driving the swarm-like seismic sequence in the Pollino range, Southern Italy

Abstract: S U M M A R YTectonic earthquake swarms challenge our understanding of earthquake processes since it is difficult to link observations to the underlying physical mechanisms and to assess the hazard they pose. Transient forcing is thought to initiate and drive the spatio-temporal release of energy during swarms. The nature of the transient forcing may vary across sequences and range from aseismic creeping or transient slip to diffusion of pore pressure pulses to fluid redistribution and migration within the sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 66 publications
7
52
0
Order By: Relevance
“…2b). In particular, between June and August 2012, about 3–4 months before the occurrence of the M W 5.1 main shock, the rate of seismicity increased faster than in the previous 2011–2012 bursts of activity 27 , which unfortunately were not covered by the geodetic measurements. The aseismic slip rate shows a synchronous increment in almost the same time period, culminating in a dramatic increase just before the 25 October 2012  M W 5.1 earthquake (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…2b). In particular, between June and August 2012, about 3–4 months before the occurrence of the M W 5.1 main shock, the rate of seismicity increased faster than in the previous 2011–2012 bursts of activity 27 , which unfortunately were not covered by the geodetic measurements. The aseismic slip rate shows a synchronous increment in almost the same time period, culminating in a dramatic increase just before the 25 October 2012  M W 5.1 earthquake (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Paleoseismological trenching studies 42, 43 on the normal faults at the southern border of the Pollino range suggest the occurrence of at least four M W  ≥ 6.5 events within the last 10,000 yr. Recent preliminary estimates of tectonic loading show that the Pollino range is actively deforming, probably slower than the Southern Apennines (the latter characterized by deformation rates up to 2–2.5 mm/yr 44, 45 ), with geodetic directions of active deformation consistent with the focal mechanisms of the largest events of the 2010–2014 Pollino swarm 27 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies of seismic swarms have also shown b value variations with time, in both natural [e.g., Wiemer et al ., ; Hainzl and Fischer , ; Passarelli et al ., ] and induced [e.g., Huang and Beroza , ] environments; however, the sense of these fluctuations varies. Wiemer et al .…”
Section: Resultsmentioning
confidence: 99%
“…The seismicity rate during swarms fluctuates over time and the largest earthquakes are usually delayed with respect to the swarm onset (Utsu, 2002;Hainzl, 2004;Vidale and Shearer, 2006;Passarelli et al, 2015aPassarelli et al, , 2018. They are thought to originate in response to stress histories more complex than a sudden stress change, e.g., due to a large earthquake, producing typical aftershock sequences (Mogi, 1967).…”
Section: Introductionmentioning
confidence: 99%